Case report: Mucormycosis due to Rhizopus microsporus: an important reminder of opportunistic infections in immunocompromised acute myeloid leukemia - Misato Higuchi; Katsutaro Nishimoto; Tomoka Waseda; Motoi Takenaka; Motoi Takenaka; Hiroyuki Murota; Hiroyuki Murota (Journal of Cutaneous Immunology and Allergy)
Hematologic malignancies, diabetes, and the development and widespread use of novel anticancer and immunosuppressive agents have introduced a new dimension of immunosuppression, raising concerns about emerging opportunistic infections. Here, we report a case of mucormycosis in a patient with therapy-related acute myeloid leukemia, encountered in our department. The patient presented with a necrotic lesion around the right eyelid. In this case, the condition and skin lesions rapidly progressed, and the patient passed away within a few days of the appearance of necrotic plaques. The causative organism was identified as Rhizopus microsporus. Mucormycosis is a severe invasive fungal infection that can rapidly worsen the prognosis of immunocompromised patients. Cutaneous mucormycosis is classified into primary and secondary forms. Based on the findings and the underlying disease, secondary cutaneous mucormycosis was suspected. Familiarity with the characteristic clinical features of mucormycosis may be the key factor in initiating timely treatment.